THE EFFECT OF FIRM CHARACTERISTICS ON THE UNDERPRICING OF IPO STOCK - Desiyanti, Rika; Hanum, Mutiara; Chrismondari; Yuliza, Mai (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
Initial Public Offerings (IPOs) represent a critical mechanism for companies to raise capital by offering their shares to the public for the first time. This study investigates the determinants of stock underpricing in IPO companies listed on the Indonesia Stock Exchange between 2019 and 2022. Specifically, we examine the impact of return on equity (ROE), firm size, firm age, and reputation in terms of Knowledge, Attitude, and Practice (KAP) on stock underpricing. The sample selection process employs a saturated sample methodology, resulting in a final observation-worthy sample of 134 companies from an initial pool of 219. We employ multiple regression analysis using the SPSS 27 program to analyze the data. Our findings reveal that while firm size, age, and KAP reputation do not significantly influence stock underpricing, return on equity emerges as a significant determinant affecting the degree of stock underpricing in IPOs. This research contributes to a better understanding of the dynamics at play in the IPO market, providing valuable insights for investors, policymakers, and market participants.